Investigation of the effect of light fastness on the color changes of maps prepared by electrophotographic digital printing - SÖNMEZ, SİNAN (WALTER DE GRUYTER GMBH, 2022)
In this study the prints were made on paper substrates, which were thought as map substrate alternatives, with 3 different surface properties at 1200 dpi by using the electrophotographic printing system. Color and gloss values of the samples were determined both before and after exposure to light for a period of 42 hours to determine the light fastness of the substrate and the print on it. The studies revealed that after the light fastness tests (i) the width of the color universe of the papers with matte surfaces is more than that of the papers with glossy surfaces, (ii) the loss of brightness of woodfree paper is higher than that of the other paper samples and (iii) the print chroma values obtained in woodfree paper is lower than those of the coated surfaces. Moreover, (iv) the delta E-00 measurements revealed that all paper samples experienced different color losses in different colors, and the most significant differences in these color losses were in magenta and black.
Keywords: cartography; color; electrophotography; light fastness; map